Exploring the experience of residents during the first six months of family medicine residency training - Martin, Dawn; Nasmith, Louise; Glover Takahashi, Susan; Harvey, Bart J. (Canadian Medical Education Journal, 2017)
Background: The shift from undergraduate to postgraduate education signals a new phase in a doctor’s training. This study explored the resident’s perspective of how the transition from undergraduate to postgraduate (PGME) training is experienced in a Family Medicine program as they first meet the reality of feeling and having the responsibility as a doctor. Methods: Qualitative methods explored resident experiences using interpretative inquiry through monthly, individual in-depth interviews with five incoming residents during the first six months of training. Focus groups were also held with residents at various stages of training to gather their reflection about their experience of the first six months. Residents were asked to describe their initial concerns, changes that occurred and the influences they attributed to those changes. Results: Residents do not begin a Family Medicine PGME program knowing what it means to be a Family Physician, but learn what it means to fulfill this role. This process involves adjusting to significant shifts in responsibility in the areas of Knowledge, Practice Management, and Relationships as they become more responsible for care outcomes. Conclusion: This study illuminated the resident perspective of how the transition is experienced. This will assist medical educators to better understand the early training experiences of residents, how these experiences contribute to consolidating their new professional identity, and how to better align teaching strategies with resident learning needs.